Enhancing the preparedness and readiness - D'Artis Kancs (Economics and Econometrics Research Institute (EERI), 2024)
To enhance the situational awareness of strategic readiness in Europe we look through two complementary angles. First, through a situational assessment of selected strategic readiness elements that have often been overlooked in Europe. Leveraging the newly augmented strategic readiness framework of the US DoD, we examine the defence industrial readiness for a protracted conflict and war, force mobility, and a sustained whole-of-society resilience. Second, through a scenario analysis in order to future-proof the strategic decision maker options to be resilient to changing boundary conditions. We stress test Europe's readiness in view of possible future systemic shocks across threat and time horizons by simulating selected scenarios of the NATO's Strategic Foresight Analysis 2023 and Future Operating Environment 2024 and evaluate potential impacts in the EU-EMS model. Situational assessment reveals that the defence industrial mobilisation, force mobility and sustained resilience readiness are "off-track" in view of the European Defence Readiness - as a steady state of preparedness. Second, by quantifying potential costs of unpreparedness, the "Cold War 2.0" scenario analysis provides a rationale for European allies to embark on a gradual de-risking trajectory rather than waiting for a much more costly "abrupt shock" trigger dictated by geopolitical events.
Keywords: H56; H57; L11; 330; Preparedness; readiness; Europe; Cold War 2.0; CRINK